Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Motivasi dan Kinerja Perangkat Desa di Kecamatan Wedi, Kabupaten Klaten - Muhammad Aga Sekamdo; Erry Setyo Prabowo; Eko Wiratno (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study aims to determine the role of leadership and work environment influence on the motivation and performance of village officials in Wedi, District, Klaten Regency, Central Java Province. The data analysis technique used is path analysis, tested by t test, F test, and R2 test, correlation, direct and indirect effects and total effect. The questionnaire data collection technique, the sample used was the village officials in Wedi District, Klaten Regency, which amounted to 50 respondents. The results showed that leadership had a positive and significant effect on work motivation of village officials, the work environment had a positive and significant effect on work motivation of village officials, leadership had a positive and not significant effect on the performance of village officials, the work environment had a positive and significant effect on the performance of village officials. Based on e1 value and e2 value, the total R2 value is 79.84%. This means that the performance of village officials is explained by the variables of leadership, work environment, motivation as an intervening or mediating variable of 79.84 and the remaining 20.16% is explained by other variables outside this study, for example organizational behavior, organizational culture, communication, education and training , and others .